KINERJA PERUSAHAAN, MANAJEMEN ASET DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM - Ayu Rahmawati; Ruhiyat Taufik; Sat Yudha Dhahana (Fakultas Ekonomi Universitas Borobudur, 2022)
Abstract The purpose of this study was to determine the effect of company performance, asset management and company size on stock returns. The sample in this study was obtained by 18 hotel, restaurant and tourism sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period with a total of 90 observations. The sampling technique used was purposive sampling. The research method used is a quantitative method using panel data regression analysis. The results showed that partially ROA had a positive and significant effect on stock returns and CR, TATO, firm size had a negative and insignificant effect on stock returns. Meanwhile, simultaneously Return On Assets, Current Ratio, Total Asset Turnover and Company Size have an effect on stock returns. Keywords: Company Performance, Return On Assets, Current Ratio, Total Asset Turnover, Company Size, Stock Return